2007
DOI: 10.1590/s1413-86702007000400011
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella enterica serovar typhi: molecular analysis of strains with decreased susceptibility and resistant to ciprofloxacin in india from 2001-2003

Abstract: Chromosomally-mediated reduced susceptibility to ciprofloxacin narrows the therapeutic options in enteric fever. We made a molecular comparison of clinical isolates of fluoroquinolone-resistant strains of Salmonella enterica serotype Typhi from January 2001 to May 2003; 178 isolates were subjected to antimicrobial susceptibility testing by the Kirby-Bauer method of disk diffusion, and agar dilution was used to determine the minimum inhibitory concentration (MIC) to ciprofloxacin. Nalidixic-acid resistant strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 23 publications
(42 reference statements)
2
25
1
Order By: Relevance
“…We showed that NA resistance increased from 0% in 1993 [16] to 15% in this study, which was similar to what was found (15%) in a report from Vietnam [25] and another (16%) from Japan [26]. However, our data were contradictory to the data reported from Nepal (76% resistance) [27], India (51% resistance) [28], the United States (39% resistance) [29], and South Africa (0.05% resistance) [30]. LEV resistance in our study (7.5%) was lower than that reported in Nepal (73%) [31].…”
Section: Discussionsupporting
confidence: 80%
“…We showed that NA resistance increased from 0% in 1993 [16] to 15% in this study, which was similar to what was found (15%) in a report from Vietnam [25] and another (16%) from Japan [26]. However, our data were contradictory to the data reported from Nepal (76% resistance) [27], India (51% resistance) [28], the United States (39% resistance) [29], and South Africa (0.05% resistance) [30]. LEV resistance in our study (7.5%) was lower than that reported in Nepal (73%) [31].…”
Section: Discussionsupporting
confidence: 80%
“…Of the 163 E. coli available sequences in the GenBank databases, we found in all instances Gly 31 , Val 44 , Asp 72 , and Lys 76 . The discrepancies between our results and those reported by Capoor and colleagues [1,6] could be caused by different numbering of the residues because the precursor GyrA protein may be processed into a signal peptide and a functional enzyme. However, this is contradicted by the numbering of the residues, Met 52 , Ser 83 , and Asp 87 , which is in accordance with an unprocessed precursor GyrA protein.…”
contrasting
confidence: 99%
“…This bacterium affects human and animals but Salmonella enterica typhimurium strain solely affects human being and there is no animal reservoir [2]. The treatment of typhi fever is done with antibiotics like ciprofloxacine [3], chloramphenicol, quinolone and cephalosporin that target the homologous proteins. Some bacterial strains of salmonella have developed resistance to one or more types of antibiotics that is increasingly becoming a problem with typhoid infections arising from south East Asia.…”
Section: Introductionmentioning
confidence: 99%